Perbandingan Efisiensi Pengendali Baterai Panel Surya PWM vs MPPT - Arsanto Narendro; Tatang Wirawan Wisnuadji; Suwasti Broto (CV. Multi Kreasi Media, 2024)
Charging controllers are utilized in various electronic systems to manage and safeguard the charging and discharging rates of batteries. For off-grid photovoltaic (PV) systems, two main technologies are employed: Pulse Width Modulation (PWM) and Maximum Power Point Tracking (MPPT). This study compares two charging controllers in PV systems with the same technical specifications to evaluate their performance under similar environmental conditions. Both controllers are built on original firmware and hardware designs, incorporating PWM and MPPT technologies. Each PV system includes a charging controller, a 30 W solar panel, and a 12V 18Ah battery. During experimental trials, voltage and current measurements were taken at both the panel and battery during charging and discharging. The findings reveal that the MPPT controller achieves a higher average efficiency than the PWM controller, indicating that the technology used in the charging controller significantly affects efficiency, even in less than ideal solar radiation and temperature conditions. While the PWM controller is a more budget-friendly option with satisfactory efficiency, the MPPT controller outperforms it in efficiency.